2001
DOI: 10.1021/es000146y
|View full text |Cite
|
Sign up to set email alerts
|

Greenland Snow Evidence of Large Scale Atmospheric Contamination for Platinum, Palladium, and Rhodium

Abstract: Since 1976 in the United States, Canada, and Japan, and later in other countries, the exhaust system of gasoline powered cars has been equipped with catalytic converters containing Pt and/or Pd and/or Rh. This has resulted in a very significant decrease in urban air pollution for various chemical species such as NOx, CO, and hydrocarbons. There has however been concern that their ever increasing use might lead to Platinum Group Metals (PGMs) becoming widely dispersed in the environment. From the analysis of Pt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
143
1
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(153 citation statements)
references
References 30 publications
1
143
1
3
Order By: Relevance
“…The annual worldwide emission of Pt, arising solely from automobile catalytic converters, has been estimated at 0.5-1.4 tons per year (Barbante et al 2001). It has been suggested that c. 99% of the Pt released from VECs is in the metallic state, with only c. 1% present as oxidized Pt, presumably as PtO 2 (Schlogl et al 1987;Artelt et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The annual worldwide emission of Pt, arising solely from automobile catalytic converters, has been estimated at 0.5-1.4 tons per year (Barbante et al 2001). It has been suggested that c. 99% of the Pt released from VECs is in the metallic state, with only c. 1% present as oxidized Pt, presumably as PtO 2 (Schlogl et al 1987;Artelt et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…For Pd, the concentration was still two times higher 50 m from the road (10 ng g −1 d.w.) than at the isolated site (5 ng g −1 d.w.), suggesting that the Pd background value was not reached before a distance of 50 m from the road. Pd particles are probably transported a long distance, as has been shown for PGE occurrence in alpine snow (Van der Velde et al, 2000) and remote Greenland snow (Barbante et al, 2001).…”
Section: Concentrations and Profiles Of Pge And Pah In Ryegrass Accormentioning
confidence: 67%
“…This deposition of Pd and PAH on the ryegrass comes from the atmosphere and demonstrates that Pd and PAH pollution occurs in all types of sites, even when the fodder is far from any sources. The Pd and PAH compounds could therefore be considered as ubiquitous in the environment and transported with particles and gases over long distances (Barbante et al, 2001).…”
Section: Concentrations and Profiles Of Pge And Pah In Ryegrass At Thmentioning
confidence: 99%
“…Studies conducted by Barbante et al [15] showed that the spread of PGMs in the environment is rather a global process, despite some works asserting the low transportability of these pollutants. Therefore, it is important to study how these PGMs species may become chemically/ biochemically active and mobile in interactions with various environmental matrices under the changing weather conditions, in order to give a prediction on the possible hazards of PGMs for human health.…”
Section: Introductionmentioning
confidence: 99%